2015
DOI: 10.9734/ijpss/2015/12828
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Exotic Rice Varieties for Genetic Parameters in a Nigerian Agro-Ecology

Abstract: Aim:The research focused on the performance of six exotic rice genotypes from Malaysian Agricultural Research and Development Institute (MARDI) in a Nigerian agro-ecology. Study Design: The varieties were evaluated in randomized complete block design replicated three times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Highest flag leaf area will increase the photosynthetic rate then yield production. These results were confirmed by Osekita et al, (2015) and Wei et al, (2020). Regarding leaf angle ( o ), the results showed that, highly significant among studied rice genotypes.…”
Section: Mean Performancesupporting
confidence: 65%
“…Highest flag leaf area will increase the photosynthetic rate then yield production. These results were confirmed by Osekita et al, (2015) and Wei et al, (2020). Regarding leaf angle ( o ), the results showed that, highly significant among studied rice genotypes.…”
Section: Mean Performancesupporting
confidence: 65%
“…The Food and Agricultural organization of the United Nations (FAO) forecasts that the global food production will need to increase by 70% if the population reaches 9.1bn by 2050 [4]. Rice being a major crop in the world, plays an important role and increase in the production of rice depends on the development of improved varieties with better productivity and adaptability, which largely depends on the existence of sufficient genetic diversity in rice germplasm [5].…”
Section: Introductionmentioning
confidence: 99%
“…Rice is a key crop in the world, and its production is dependent on the development of superior varieties with greater productivity and adaptability, which is largely dependent on the presence of sufficient genetic variation in rice germplasm (Osekita et al, 2015). This is normally performed through hybridization following that in segregating populations in selecting plants with favorable qualities (Becerra et al, 2017)Chile, has a rice (Oryza sativa L.. Rice accessions include a large number of beneficial genes that rice breeders can employ to improve the crop and genetic heterogeneity exists among rice accessions allowing for a wide range of agricultural improvements.…”
Section: Introductionmentioning
confidence: 99%